Inspiration Clones literature: Tracing the imprints of Bob Dylan’s Song on Joyce Carol Oates’s Story (Siddhajyoti Interdisciplinary Journal, 2021)
Drawn by the dedication of Joyce Carol Oates’s story “Where Are You Going, Where Have You Been?” to Bob Dylan and motivated by her later admission regarding the inspiration of Dylan’s song “It’s All Over Now, Baby Blue” to write the story, the study examines how the song has transmitted its imprints on the story. Inspiration is the theoretical framework for the study, which has been diversely explained by various theorists incorporating its elusive nature. However, they have a common understanding of its role as a necessary condition for creativity. This inquiry synthesizes the literature associated with the song and the story, analyzes the theories related to creative inspiration, and scrutinizes the reiteration of evidence from the seminal song in the story. The reiteration of context, character, and imagery of the song in the story infers the whole story as literary cloning of the song. Ultimately, the study contributes to understanding how a form of art facilitates the audience not only offering joy but also inspiring them for their further creative process and how the seminal work reappears as metamorphosis.